A dimensão subjetiva da escolha moral na adolescência - Otuka, Flávia de Souza (2009)
This work is the result of the empiric research, tha analised the subjectivity dimensions of the moral choice in the adolescense and, therefore it capturedthe values used to the groundings of the options made by the youngling. For that, it was necessary the use of the sense rate. From the sense analysis, we identified the proximity or the detachment of the subject, that was Agnes Heller (2006) called uniqueness and individuality. We stand for the theory approach of the Socio historic Phycology and in the sociology of Agnes Heller. The research was made with 9 teenagers in the last High school year of a public school. The methods used to collect information were: 1) present the movie Lord of the Flies to a group containing 9 students; 2) implementation of 2 later meetings with the same group to debate the fiction movie contents. From these 3 meetings, two teenagers that reached the best conditions to the research were picked; 4) individual interviews were made with the two choosen teenagers. We used as procedure of analysis, what Aguiar and Ozella (2006) called of meaning core construction. We verified that the knoledge earned with the interviews about those two teenagers, allowed a better understanding of the actions and contradictions lived by them in the group. In the same way, the group situation analysis let us capturewith more effect the elements that came out during the interviews. Ending the analysis procedure we performed na analytic assay talking about the group and individual results to point the understanding of the subjectivity dimension, allows to keep the peculiar motion of the subject in the group, at the same time, the knoledge gained with the group motion sense helped to understand the individial actions. Our analysis showed, amond other things,that the interviewed younglings presented an idea of the naturalized man, placeing great expectations in the social rise through education, they realise the school education as a possibility to work and, in general, they tende to act in the particularity field, although they show several actions in the individual field